Analisis dampak kompetensi guru pada implementasi pendidikan karakter siswa kelas rendah selama pembelajaran daring di sekolah dasar - Sari Ilham Wardani; Hadi Mulyono; Fadhil Purnama Adi (Didaktika Dwija Indria, 2021)
The purpose of the research was to analyzed and described the impact of teacher’s competence as an attempt to implementation character building on low-grade student during online learning. This research study is qualitative descriptive with qualitative case study methods. The data and source data was collected from the low-grade teacher that consisted of teacher of class I, II and III SD Negeri Totosari. The data of the research obtained used data collection interview, observation and documentation. This research used triangulation technique as the validity data research. This study using analysis interactive data Miles and Huberman. Procedure of the research used case study methods by Cresswell. The result of the research indicated that the teacher’s competence has many impacts to implementation of the character-building on low-grade student during online learning, teacher with a good competence will able to organize how the student’s activity that favour to character building during online learning can work effectively but the teacher with a low competence was lacked on organized how the activity class to favour character building during online learning well.